(untitled) (Research, Society and Development, 2021)
Due to the great economic potential of the yellow cherry guava as a supplier of healthy food and possible pharmaceutical uses, the study of means of reproduction of the species becomes of interest for its diffusion in crops. The objective of this work was to evaluate the effect of gibberellin and benzylaminopurine on the germination process of yellow cherry guava, Ya-cy variety. The study was carried out at the Universidade Tecnológica Federal do Paraná - Dois Vizinhos, with yellow cherry guava seeds, Ya-cy variety. The experimental design was completely randomized, in factorial 2 x 3 (hormone x concentration), with four replicates of 100 seeds. The hormones used were 6-benzylaminopurine (BAP) and gibberellic acid (GA3) at concentrations of 0, 50 and 100 mg L-1. It was also evaluated the effect of the storage of these for 20 days in refrigerator, being considered the control treatment. The experiment was conducted in the Laboratory of Plant Physiology with seeds placed to germinate in gerbox boxes in chamber B.O.D. The percentage, speed index and average germination time were evaluated. For the yellow cherry guava Ya-cy it is not necessary to use benzylaminopurine to alter the germinative processes. It is recommended to use 50 mg L-1 of gibberellins or cold stratification for better germinative responses.